External Imbalances and Financial Crises - Taylor, Alan (IMF Working Papers; Working Paper ;, 2013)
Consider two views of the global financial crisis. One view looks across the border: it blames external imbalances, the unprecedented current account deficits and surpluses in recent years. Another view looks within the border: it faults domestic financial systems where risks originated in excessive credit booms. We can use the lens of macroeconomic and financial history to confront these dueling hypotheses with evidence. The credit boom explanation is the most plausible predictor of crises since the late nineteenth century; global imbalances have only a weak correlation with financial distress compared to indicators drawn from the financial system itself.